TEACHERS’ STRICTNESS AND ITS IMPACT ON LEARNING OUTCOMES: A CRITICAL REVIEW - Salainti, Engelina; Sanger, Allan Hubert Frederick (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Teachers’ strictness has a role in shaping students' learning and has become an extensive research subject of education. This research is focused on teachers' strictness, which impacts the students' engagement, academic achievements, and emotions. Findings showed that the balancing of approach where strictness, support, and clear communication can impact the students' achievement and their behavioral development positively. The method of strict discipline may lead to the effect of decreased motivation, lower engagement, and increased anxiety. For example, research highlights that strict class management can enhance short-term compliance, otherwise, this matter destroys long-term educational achievement, except if it is combined with the nurture of the relationship between teacher and students. Furthermore, the education strategy that interprets discipline and empathy is recommended to foster a conducive environment for the development of the students holistically. These findings underlined the complexity of the effectiveness of the teacher which advocates a nuanced approach of discipline that supports academic rigor and emotional support.